Pengaruh CAR, LDR dan NPL Terhadap Profitabilitas Bank BUMN Indonesia Periode 2019–2024 - Sherly Putri J; Soritaon; Dudi Hendaryan (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
The profitability of state-owned banks plays an important role in maintaining the stability of the national financial system, particularly during periods of crisis and post-pandemic economic recovery. A bank’s ability to generate profit serves as a key indicator in assessing the effectiveness of asset management, capital adequacy, liquidity, and credit risk management. This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non-Performing Loan (NPL) on Return on Assets (ROA) in state-owned banks during the 2019–2024 period. The research employed a quantitative approach using panel data regression analysis to examine the relationship between CAR, LDR, NPL, and ROA. The sample consisted of four state-owned banks listed on the Indonesia Stock Exchange with a total of 24 observations. The results indicate that CAR, LDR, and NPL partially and simultaneously do not have a significant effect on ROA. The coefficient of determination of 10.57% suggests that other factors, such as operational efficiency and macroeconomic conditions, play a more dominant role in influencing bank profitability